2011
DOI: 10.1105/tpc.111.086389
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Rhizobia Bacteria Trigger a Change in Localization and Dynamics of the Medicago truncatula Receptor Kinase LYK3

Abstract: To form nitrogen-fixing symbioses, legume plants recognize a bacterial signal, Nod Factor (NF). The legume Medicago truncatula has two predicted NF receptors that direct separate downstream responses to its symbiont Sinorhizobium meliloti. NOD FACTOR PERCEPTION encodes a putative low-stringency receptor that is responsible for calcium spiking and transcriptional responses. LYSIN MOTIF RECEPTOR-LIKE KINASE3 (LYK3) encodes a putative high-stringency receptor that mediates bacterial infection. We localized green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
78
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 64 publications
(112 reference statements)
8
78
1
2
Order By: Relevance
“…Therefore, it is plausible that the active GTP-bound ROP10 is partitioned into lipid rafts of the PM. Current evidence also supports the association of NF receptors with lipid rafts, such as the colocalization of LYK3 and the lipid raft-localized flotillin-like proteins FLOT2 and FLOT4 (Haney et al, 2011) and the interaction of a symbiotic remorin protein SYMREM1 with NFP and LYK3 in the raft during infection (Lefebvre et al, 2010). Thus, we hypothesize that GTPbound ROP10 is also recruited to lipid rafts during infection, where it forms a protein complex with NF receptors and associated proteins.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, it is plausible that the active GTP-bound ROP10 is partitioned into lipid rafts of the PM. Current evidence also supports the association of NF receptors with lipid rafts, such as the colocalization of LYK3 and the lipid raft-localized flotillin-like proteins FLOT2 and FLOT4 (Haney et al, 2011) and the interaction of a symbiotic remorin protein SYMREM1 with NFP and LYK3 in the raft during infection (Lefebvre et al, 2010). Thus, we hypothesize that GTPbound ROP10 is also recruited to lipid rafts during infection, where it forms a protein complex with NF receptors and associated proteins.…”
Section: Discussionsupporting
confidence: 57%
“…Apart from the well-studied clathrin-dependent endocytosis (Chen et al, 2011), other entry pathways, including membrane raftmediated endocytosis, also operate in plant cells (Murphy et al, 2005;Moscatelli et al, 2007;Bandmann and Homann, 2011). Recent studies suggested that plant flotillins play a critical role in symbiotic bacterial infection of M. truncatula (Haney and Long, 2010;Haney et al, 2011), and the recycling of PIN proteins may depend on structural sterols and membrane rafts in Arabidopsis Willemsen et al, 2003;Men et al, 2008). Although these studies have begun to provide insights into the role of endocytosis in plants, the molecular mechanisms underlying these events remain to be elucidated.…”
Section: Flot1 Participates In Non-clathrin-mediated Endocytosismentioning
confidence: 99%
“…Recent studies reported that misexpression of the membrane raft protein remorin altered virus propagation (Borner et al, 2005;Raffaele et al, 2009;Titapiwatanakun et al, 2009), and plant flotillins appear to play a critical role in symbiotic bacterial infection in M. truncatula (Haney and Long, 2010;Haney et al, 2011). Arabidopsis flotillin1 (Flot1), a protein first identified in DRMs using subcellular fractionation, two-dimensional electrophoresis, and mass spectrometry, is considered to be one such membrane microdomain protein (Borner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria enter the root hair following localized cell wall hydrolysis (Xie et al, 2012) within an inward-growing channel known as the infection thread. At the biochemical level, Nod factors elicit a complex series of changes, including ion fluxes at the root hair tip (Felle et al, 1998), periodic increases in intracellular calcium within and around the nucleus (Ehrhardt et al, 1996;de Ruijter et al, 1999;Wais et al, 2000), rearrangement of the root hair cytoskeleton (CĂĄrdenas et al, 1998;Timmers et al, 1999), changes in phosphorylation profiles , modification of membrane protein dynamics (Haney et al, 2011), and induction of cortical cell divisions (Ehrhardt et al, 1992;Timmers et al, 1999, and refs. therein).…”
mentioning
confidence: 99%
“…Nod factor receptors, which include Lysine motif domain-containing receptorlike kinase3 (LYK3) and Nodulation factor perception (NFP) in Medicago truncatula and Nodulation factor receptor1 (NFR1) and NFR5 in Lotus japonicus, are plasma membrane-localized receptor-like kinase and kinase-like (RLK) proteins (Amor et al, 2003;Smit et al, 2007;Haney et al, 2011;Moling et al, 2014) consisting of an intracellular kinase domain and an extracellular region with two or three chitin-binding Lys motifs (LysM). LysM domains bind Nod factors through their chitin backbone (Petutschnig et al, 2010;Broghammer et al, 2012) and are implicated in Nod factor recognition specificity .…”
mentioning
confidence: 99%